Clay mineral evidence for sediment provenance and the evolution of the East Asian Winter Monsoon in the central Philippine Sea over the last 4.38 Ma - Jun Sun; Fei Guo; Huaichun Wu; Wei Huang; Jian Liu; Kai Lu; Jingfang Lu; Shuang Sun; Meinan Shi; Boya Li; Liwei Liu; Xiaoke Qiang (Global and Planetary Change, 2026)

The individual and combined effects of coastline changes and riverine input on water quality: A multi-scenario simulation perspective - Jingfang Lu; Wei Zheng; Dehai Song; Xianqing Lv; Weimin Wang; Honghua Shi (Marine Pollution Bulletin, 2025)

Carbon-confinement modulated interfacial water structure for accelerated dissociation kinetics towards hydrogen evolution - Fanpeng Cheng; Yue Yu; Yulu Wan; Dashuai Wang; Shangqing Chen; Jingfang Zhang; Huijuan Guo; Yang Xia; Yi Huang; Lijuan Shi; Liwei Cheng; Qun Yi (Chemical Engineering Journal, 2025)

Transcriptome sequence reveal the roles of MaGME777 and MabHLH770 in drought tolerance in Musa acuminata - Yuchen Wei; Jingfang Shi; Xueyi Xie; Feng Zhang; Huizhen Dong; Yaoyao Li; Fangcheng Bi; Xiaosan Huang; Tongxin Dou (Plant Science, 2025)

Electron beam and X-ray irradiation promote extraction of bioactive compounds from walnut green husk: Structural, physicochemical, and functional properties - Ruolin Wang; Heyu Shen; Junqing Bai; Guangming Zou; Yubing Shi; Jingfang Ao; Heting Qi; Yingying Cai; Anwei Luo (Food Bioscience, 2024)

High Frequency of Autoantibodies in COVID-19 Patients with Central Nervous System Complications: a Multicenter Observational Study - Jingfang Lin; Dong Zheng; Decai Tian; Pei Zheng; Hongya Zhang; Chuo Li; Chunliang Lei; Fudong Shi; Honghao Wang (Molecular Neurobiology, 2024)

Spatio-temporal changes and driving forces of reclamation based on remote sensing: A case study of the Guangxi Beibu Gulf - Jingfang Lu; Yibo Zhang; Honghua Shi; Xianqing Lv (Frontiers in Marine Science, 2023)
Since 2000, coastal reclamation projects have been implemented in the Guangxi Beibu Gulf to alleviate the shortage of coastal land resources. As a result, the reclamation area has increased significantly. In this study, based on the Landsat program, we tracked coastal reclamation in the coastal waters of Guangxi in the 21st century. An indicator system was proposed to assess the driving forces of reclamation synthetically. Our results showed that 98.6 km 2 of coastal waters of the Guangxi Beibu Gulf was reclaimed from 1997 to 2017, in which three regions underwent great changes: Fangcheng Bay, Tieshan Bay, and Qiznhou Bay. Furthermore, spatio-temporal changes of reclamation were affected by the combination of population growth, economic development, and marine industry development in coastal cities. These results provide an important historical reference for tracking the human development processes of the Guangxi Beibu Gulf, and also offer some suggestions for the rational allocation of reclamation resources.

The inhibitory mechanism of pentacyclic triterpenoid acids on pancreatic lipase and cholesterol esterase - Heyu Shen; Jun Wang; Jingfang Ao; Lixia Ye; Yubing Shi; Yujie Liu; Mengyang Li; Anwei Luo (Food Bioscience, 2023)

Coastal vulnerability modelling and social vulnerability assessment under anthropogenic impacts - Jingfang Lu; Yibo Zhang; Honghua Shi; Xianqing Lv (Frontiers in Marine Science, 2022)
Coastal regions are highly vulnerable to the impacts of human activities, land cover change, sea level rise (SLR), and climate extremes. In this study, we attempt to address this issue by simulating the spatial interactions among natural hazards, ever-increasing human activities, and social vulnerability in the south coast of the Bohai Sea, China. It is found that the activities occurring on land, especially within coastal environments, such as agricultural pond and ports, and those in the ocean (tide and residual current) both impose disaster risks on the marine environment. In 2020, 25.2% of the total study area is highly vulnerable, which is 21% larger than that in 1997. The socially vulnerable areas are mainly distributed in the southeast coast of the Laizhou Bay. These areas should be strengthened to reduce and prevent the storm surge and flood disasters. Ultimately, we emphasize the urgent needs to implement effective policy measures for reducing tomorrow’s risks from natural hazards.

Increased greenhouse gas emissions intensity of major croplands in China: Implications for food security and climate change mitigation - Jingting Zhang; Hanqin Tian; Hao Shi; Jingfang Zhang; Xiaoke Wang; Shufen Pan; Jia Yang (Global Change Biology, 2020)
Balancing crop production and greenhouse gas (GHG) emissions from agriculture soil requires a better understanding and quantification of crop GHG emissions intensity, a measure of GHG emissions per unit crop production. Here we conduct a state‐of‐the‐art estimate of the spatial‐temporal variability of GHG emissions intensities for wheat, maize, and rice in China from 1949 to 2012 using an improved agricultural ecosystem model (Dynamic Land Ecosystem Model‐Agriculture Version 2.0) and meta‐analysis covering 172 field‐GHG emissions experiments. The results show that the GHG emissions intensities of these croplands from 1949 to 2012, on average, were 0.10–1.31 kg CO 2 ‐eq/kg, with a significant increase rate of 1.84–3.58 × 10 –3 kg CO 2 ‐eq kg −1 year −1 . Nitrogen fertilizer was the dominant factor contributing to the increase in GHG emissions intensity in northern China and increased its impact in southern China in the 2000s. Increasing GHG emissions intensity implies that excessive fertilizer failed to markedly stimulate crop yield increase in China but still exacerbated soil GHG emissions. This study found that overfertilization of more than 60% was mainly located in the winter wheat–summer maize rotation systems in the North China Plain, the winter wheat–rice rotation systems in the middle and lower reaches of the Yangtze River and southwest China, and most of the double rice systems in the South. Our simulations suggest that roughly a one‐third reduction in the current N fertilizer application level over these “overfertilization” regions would not significantly influence crop yield but decrease soil GHG emissions by 29.60%–32.50% and GHG emissions intensity by 0.13–0.25 kg CO 2 ‐eq/kg. This reduction is about 29% and 5% of total agricultural soil GHG emissions in China and the world, respectively. This study suggests that improving nitrogen use efficiency would be an effective strategy to mitigate GHG emissions and sustain China's food security.